2008
DOI: 10.1242/jeb.019141
|View full text |Cite
|
Sign up to set email alerts
|

Inductive transcription and protective role of fish heme oxygenase-1 under hypoxic stress

Abstract: SUMMARYHeme oxygenase-1 is the rate-limiting enzyme in the degradation of heme into biliverdin, carbon monoxide and free divalent iron. In this study, we cloned heme oxygenase isoform 1 (CaHO-1) from a hypoxia-tolerant teleost fish Carassius auratus. The fulllength cDNA of CaHO-1 is 1247 bp and encodes a protein of 272 amino acids. RT-PCR and real-time PCR analysis indicated that CaHO-1 was predominantly transcribed in posterior kidney, head kidney, gill and intestine, and induction of gene transcription was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The data suggested that SVCV infection could down-regulate the expression level of HO-1. As demonstrated by previous reports, fish HO-1 played a significant protective role in the cells in response to the hypoxic stress [15] or toxicity [16], suggesting that the fish HO-1 gene is pleiotropic and may be involved in cytoprotection against oxidative stress.…”
Section: Discussionsupporting
confidence: 59%
“…The data suggested that SVCV infection could down-regulate the expression level of HO-1. As demonstrated by previous reports, fish HO-1 played a significant protective role in the cells in response to the hypoxic stress [15] or toxicity [16], suggesting that the fish HO-1 gene is pleiotropic and may be involved in cytoprotection against oxidative stress.…”
Section: Discussionsupporting
confidence: 59%
“…Wang et al [86] cloned the hypoxia-induced HO-1 gene in the crucian carp. Using cell lines, they found that HO-1 plays an important role against hypoxia-induced cell death.…”
Section: Hypoxia Adaptation Mechanisms In Fishesmentioning
confidence: 99%
“…The HO-1/CO system, however, has been well conserved throughout all vertebrates. The amino acid protein sequence of zebrafish (D. rerio) HO-1 bears an 86% identity with goldfish (Carassius auratus; Wang et al, 2008), 60% with Xenopus (Shi et al, 2008) and approximately 50% when compared with mammalian and avian protein sequences (reviewed in Olson et al, 2012). Furthermore, the amino acid sequence of the 'HO signature motif', believed to be important for heme binding and catabolism, shares 92-96% similarity between all vertebrate species investigated to date (Wang et al, 2008).…”
Section: Ho-1/co System In Other Vertebratesmentioning
confidence: 99%
“…The amino acid protein sequence of zebrafish (D. rerio) HO-1 bears an 86% identity with goldfish (Carassius auratus; Wang et al, 2008), 60% with Xenopus (Shi et al, 2008) and approximately 50% when compared with mammalian and avian protein sequences (reviewed in Olson et al, 2012). Furthermore, the amino acid sequence of the 'HO signature motif', believed to be important for heme binding and catabolism, shares 92-96% similarity between all vertebrate species investigated to date (Wang et al, 2008). Physiological control by endogenously produced CO is not restricted to mammalian vertebrates but is also involved in control of vascular tone and breathing in fish (Dombkowski et al, 2009;Tzaneva and Perry, 2014), retinal pathways and neuromuscular transmission in amphibians (Pong and Eldred, 2009;Sitdikova et al, 2007; reviewed in Sitdikova and Zefirov, 2012), and learning and vascular control in birds (Cutajar et al, 2005;Van der Sterren et al, 2011).…”
Section: Ho-1/co System In Other Vertebratesmentioning
confidence: 99%